Extraction Temperature Effect in Modification of Nephelium Tannin Based Biosorbent - Yanti, I.; Winata, W.F.; Zahrahyanti, M.; Nurfatimah, R.A. (Asian Journal of Chemistry, 2017)
The effect of temperature on the extraction process of nephelium peel in the modification nephelium tannin based biosorbent (NTBB) from the nephelium peel was done by varying the temperature of the extraction. Modified nephelium tannin based biosorbent carried by the cross-linker using formaldehyde and performed stability of nephelium tannin based biosorbent by varying the pH system. The results of cross-link process between tannin extract and formaldehyde compounds to produce nephelium tannin based biosorbent which were characterized using infrared spectrophotometer. The characterization result by infrared spectrophotometer shown extraction temperature of tannin from the nephelium peel affected the formation of nephelium tannin based biosorbent functional groups. The higher extraction temperature cause HCN will be released and attached on nephelium tannin based biosorbent polymer that was detected by IR spectra. The stability of nephelium tannin based biosorbent in solution shows that nephelium tannin based biosorbent will easily dissolve in the system of high acidity so that it will form a high peak at a wavelength of 240-280 nm using a UV-visible spectrophotometer, where nephelium tannin based biosorbent optimum stability in solution occurs at pH 5.